Interventions to Achieve the Untapped Potential of Conservation Agriculture in India - Vijayakumar, S.; Gobinath, R.; Kumar, S. Arun; Bandeppa, S.; Gompa, S. Jasudas; Basavaraj, K.; Prakasam, V.; Manasa, Vakada (Chronicle of Bioresource Management, 2023)
With the increasing population, dependency on natural resources are surging exponentially, especially agriculture resources are declining in a diminishing way. The researchers have developed many concepts to conserve the resources while increasing the productivity. Among the many initiatives, conservation agriculture gained more attention due to its efficiency and positive impact on soil health. Conservation agriculture (CA) is a new paradigm for agricultural research and development in India, as opposed to the traditional one, which was primarily focused on meeting specific food grain production targets. A paradigm shift has become necessary to increase production with little damage to available natural resources and the environment. Integrating productivity, resource conservation, soil quality and environmental issues is now essential for long-term productivity increase. However, how best the CA technologies can be adopted by farmers will mainly depend on socio-economic and biological feasibility apart from the adjustment in existing systems and issues related to risk management.